Investigation of the Relationship Between Breast Cancer Awareness and Health Literacy in Female Textile Workers - Ayla Hendekci (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: The level of breast cancer awareness among female may vary depending on their level of health literacy.Aim: It was aimed to investigate the relationship between breast cancer awareness and health literacy among female textile workers.Method: This study was a cross-sectional study. The study population consisted of female employed as workers in a textile company. The sample included 360 female workers as participants. The Information Form, the Breast Cancer Awareness Scale, and the Health Literacy Scale are the data collection instruments used in the study. Independent samples t-test, ANOVA, and regression analyses were used to evaluate the data.Results: The results were that 73.6% of the participants did not perform regular breast self-examination, and 55.3% had information on early diagnosis and treatment. Signifiant positive correlations were observed between women's breast cancer awareness and the functional (r = 0.135; p = 0.011), interactive (r = 0.145; p = 0.006), and critical (r = 0.156; p = 0.003) sub-scales of health literacy. According regression analysis to the established model, an increase in health literacy scores corresponded to increased breast cancer awareness, explaining 3.9% of the variation. Conclusion: It was revealed that as the health literacy of working female increases, breast cancer awareness will increase. Therefore, the focus should be on supporting the health literacy of women in the risk group, reaching more women in collective institutions and breast cancer awareness activities.